Penokohan dalam Novel Lima Sekawan yang Melacak Jejak Rahasia Karya Enid Blyton - Jeverson Nawa Wanyi; Richard Oematan; Sanhedri Boimau (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The problem raised in this study is: How is the characterization in the novel "The Famous Five: Five on a Secret Trail" by Enid Blyton? The aim of this study is to provide a comprehensive description of the characterization in the novel "The Famous Five: Five on a Secret Trail" by Enid Blyton. The theory used in this study is psychoanalytic theory with a psychological approach. This theory was introduced by Sigmund Freud, which states that an individual's personality is formed by three elements. These influencing elements consist of the "Id" as innate instinct, the "Ego" as the personality system that acts as a guide for the individual toward reality, and the "Superego" as the moral principle. The method used in this study is a descriptive qualitative method. The data collection technique used in this study is the technique of reading the novel "The Famous Five: Five on a Secret Trail" by Enid Blyton. Based on the results of the study, it can be concluded that the characters in the novel "The Famous Five: Five on a Secret Trail" by Enid Blyton can be divided into two categories: main characters and supporting characters. The main character in the novel "The Famous Five: Five on a Secret Trail" by Enid Blyton is Julian, who has a wise character. His psychological element is the ego. Meanwhile, the supporting characters are: (1) George, who has a caring and easily offended character. Her psychological elements are the ego and id. (2) Anne, who has a timid disposition. Her psychological element is the id. (3) Dick, who has a humorous character. His psychological element is the id. (4) Uncle Quentin, who has an irritable disposition. His psychological element is the id. (5) Aunt Fanny, who has a caring character. Her psychological element is the superego. (6) Guy, who has a rough disposition. His psychological element is the id. (7) Harry, who has a caring disposition. His psychological element is the superego. (8) The Inspector, who has a wise character. His psychological element is the ego. The results of this study are expected to be beneficial for Indonesian language and literature teachers as learning material, particularly in analyzing literary works from the aspect of characterization using psychological theory.